Evaluasi Penerapan Kompensasi pada Karyawan (Studi Kasus Pada Perusahaan Distribusi Pakan Kuda) - Yasmin Nurul Haq Almuqayyim; Tini Kartini (MANAJEMEN, 2026)
This study aims to determine the implementation of the employee compensation system in a horse feed distribution company. The problems identified include compensation. This study used a descriptive qualitative approach to obtain an overview of the company's compensation system. Data collection techniques included interviews, observation, documentation, and a literature review. The study's findings indicate that the suboptimal compensation system has resulted in low employee motivation and performance, as well as inconsistent achievement of the company's revenue targets. The company has made gradual improvements, but further improvements are still needed. Therefore, this study recommends improving the compensation policy through salary adjustments in accordance with the Bogor Regency minimum wage, more systematic bonus management, welfare benefit planning, and improved work facilities to support optimal achievement of the company's targets